(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
The vegetal world is described in this research article as the interaction with critical plant studies that undermines the human-centric worldview. The main goal of this article is to reassess the nature of flowers by returning to the flowers themselves in Virginia Woolf’s Mrs. Dalloway, which is oddly relevant to humankind. The novel’s floral and human interactions with flowers have been analysed using Friedrich Nietzsche’s "perspectivism" and Michael Marder’s theoretical idea of "vegetal phenomenology."Regardless of human interference, Marder’s notion guides the research towards the perception of flowers. Humans are not a prerequisite for the existence of flowers, which exist independently of humans. Nietzsche advocated perspectivism, which holds that all points of view are legitimate and that any dominant position ought to be disregarded. Multispecies ethnography, of course, is the analysis method that grants the species on Earth agency. The interaction between non-human and human species makes up the analytical framework. The two strings of the analytical thread are the floral replies, which ask how humans have benefited from flowers and how the flowers have manifested themselves in the presence or absence of humans. Multispecies ethnography, of course, is the analysis method that grants the species on Earth agency. This study suggests that viewing the world only with the human eye is a tedious and exhausting experience. Once more, adopting a floral perspective would elevate human epistemological standing. There would be a greater reservoir of floral knowledge, of course.